Factors Influencing the Increasing Disparity in LDL Cholesterol Control Between White and Black Patients With Diabetes in a Context of Active Quality Improvement. (July 2014) - Zhang, Raymond; Lee, Ji Young; Jean-Jacques, Muriel; Persell, Stephen D.
After implementing a multifaceted physician-directed quality improvement (QI) initiative, an increased disparity in low-density lipoprotein (LDL) cholesterol control between white and black diabetes patients was observed. To examine possible causes, a retrospective analysis of 962 black and white patients treated continuously between 2008 and 2010 was performed. At baseline, 55.0% of whites and 49.8% of blacks were controlled (5.2% disparity). The disparity increased, with 61.8% of whites and 44.6% of blacks having control in 2010 (17.2% disparity). Among patients uncontrolled at baseline, blacks were less likely to become controlled. Among patients controlled at baseline, blacks were less likely to remain controlled; accounting for patient characteristics and changes in lipid-lowering drug prescription regimens did not attenuate these relationships. Physician-facing, general QI interventions may be insufficient to produce equity in LDL cholesterol control. Helping patients maintain prior success controlling cholesterol appears as important in addressing this disparity as is helping uncontrolled patients achieve control.